2018
DOI: 10.1186/s12944-018-0701-0
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal dexamethasone and postnatal high-fat diet have a synergistic effect of elevating blood pressure through a distinct programming mechanism of systemic and adipose renin–angiotensin systems

Abstract: BackgroundHypertension may result from high-fat (HF) diet induced-obesity and overexposure to glucocorticoids in utero. Recent studies demonstrated the potent contribution of adipose tissue’s renin-angiotensin system (RAS) to systemic RAS, which plays a key role in regulating blood pressure (BP). In this study, we investigated the effects of prenatal dexamethasone (DEX) exposure and postnatal HF diet on RAS of adipose tissue.MethodsRAS and BP of 6-month old rats exposed to prenatal DEX and/or postnatal HF diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 61 publications
(52 reference statements)
1
47
2
Order By: Relevance
“…The mRNA levels in mice livers were assessed, and it was observed that ACE2 gene expression was reduced in the HFD group compared with the control group (11). Similarly, another study in the retroperitoneal adipose tissue of postnatal rats found that consumption of an HFD downregulated ACE2 gene expression (41). Research has also demonstrated that an HFD can lead to reduced kidney ACE2 activity only in male mice and further demonstrated that the ovariectomy of female mice fed an HFD led to reduced adipose ACE2 activity (13).…”
Section: Biological Plausibility For Gene-diet Interactionsmentioning
confidence: 96%
See 4 more Smart Citations
“…The mRNA levels in mice livers were assessed, and it was observed that ACE2 gene expression was reduced in the HFD group compared with the control group (11). Similarly, another study in the retroperitoneal adipose tissue of postnatal rats found that consumption of an HFD downregulated ACE2 gene expression (41). Research has also demonstrated that an HFD can lead to reduced kidney ACE2 activity only in male mice and further demonstrated that the ovariectomy of female mice fed an HFD led to reduced adipose ACE2 activity (13).…”
Section: Biological Plausibility For Gene-diet Interactionsmentioning
confidence: 96%
“…With ACE2 as the cellular receptor for SARS-CoV, the interaction between the virus and ACE2 impacts its entrance and clearance (29,45). ACE is responsible for the cleavage of AngI into AngII (34,37), and following this process, ACE2 generates Ang (16,23,29,30,39,41,43) from a single residue cleavage of AngII and then acts as a negative regulator (8). This phenomenon has been demonstrated in mouse models, whereby disrupting the murine ACE2 gene leads to increased levels of AngII (6).…”
Section: Biological Plausibility For Gene-diet Interactionsmentioning
confidence: 99%
See 3 more Smart Citations